2020
DOI: 10.3389/fpsyt.2020.00870
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Reliability and Validity of the DMRS-SR-30, a Novel Self-Report Measure Based on the Defense Mechanisms Rating Scales

Abstract: Defense mechanisms are psychological factors that influence emotional distress and quality of life. There are a number of measures assessing the construct of defense mechanisms, but only few available instruments reflect the gold-standard theoretical hierarchical organization of defenses. We report on the development of a novel 30 item self-report questionnaire, the DMRS-SR-30, based on the parent instrument, the Defense Mechanism Rating Scales (DMRS). This study tested preliminary reliability and validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 81 publications
5
61
0
1
Order By: Relevance
“…Furthermore, the economic downturn caused by this emergency is more likely to impact sectors with high female employment shares, together with the increasing needs in childcare (Alon et al, 2020). Finally, our findings suggested that lockdown duration has a negative impact on mental health; a previous study displayed in the first phase of the Italian quarantine had already reported that individuals in quarantine experienced negative psychosocial changes such as sleep disturbances, post-traumatic symptoms, depression, and anxiety which all have a massive impact on wellbeing (Brooks et al, 2020;Cellini et al, 2020;Wang et al, 2020;Di Giuseppe et al, 2020d).…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, the economic downturn caused by this emergency is more likely to impact sectors with high female employment shares, together with the increasing needs in childcare (Alon et al, 2020). Finally, our findings suggested that lockdown duration has a negative impact on mental health; a previous study displayed in the first phase of the Italian quarantine had already reported that individuals in quarantine experienced negative psychosocial changes such as sleep disturbances, post-traumatic symptoms, depression, and anxiety which all have a massive impact on wellbeing (Brooks et al, 2020;Cellini et al, 2020;Wang et al, 2020;Di Giuseppe et al, 2020d).…”
Section: Discussionsupporting
confidence: 49%
“…The levels, ranging from most to least adaptive, are: adaptive/mature, obsessional, neurotic, minor image-distortion/narcissistic, disavowal, major imagedistortion/borderline, and action. The psychometric properties of this DMRS-SR-30 are robust, with internal consistency ranging from good to excellent across all subscales and strong convergent and divergent validity (Di Giuseppe et al, 2020b). Somatization was measured with the PHQ-15 (Kroenke et al, 2002) which asks about 15 somatic symptoms that account for 90% of the symptoms reported in outpatient settings (Kroenke, 2003).…”
Section: Implicit Emotion Regulationmentioning
confidence: 99%
“…Understanding how the ongoing pandemic is influencing human reactions to such a stressful event is essential for developing ad hoc effective interventions. The systematic assessment of unconscious psychological aspects of personality should be promoted for the early detection of vulnerable individuals and for improving research and clinical practice toward a personalized therapeutic approach (Lingiardi and McWilliams, 2015 ; Lingiardi et al, 2015 ; Tanzilli et al, 2016 ; Barber and Solomonov, 2019 ; Talia et al, 2019 ; Di Giuseppe et al, 2020c ; Zilcha-Mano and Ramseyer, 2020 ).…”
Section: Discussionmentioning
confidence: 99%